The stock selection problem: Is the stock selection approach more important than the optimization method? Evidence from the Danish stock market - Klaus Grobys (Journal of Applied Finance & Banking, 2011)
Passive investment strategies basically aim to replicate an underlying benchmark. Thereby, the management usually selects a subset of stocks being employed in the optimization procedure. Apart from the optimization procedure, the stock selection approach determines the stock portfolios' out-of-sample performance. The empirical study here takes into account the Danish stock market from 2000-2010 and gives evidence that stock portfolios including small companies' stocks being estimated via cointegration optimization methods are most beneficial. Only the stock portfolios exhibiting the lowest initial market capitalization corresponding to 29.51% showed a Sharpe ratio of 0.4545 and 0.4824, respectively, being higher than the stock market's Sharpe ratio of 0.4451 concerning the out-of-sample period running from 2003-2010.
Keywords: C13; C22; G11; G12; 330; stock selection; optimization procedure; cointegration; quasi-maximum-likelihood estimation; index-tracking